Impact of urbanization on tropical mesoscale events: investigation of three heavy rainfall events - Prashant Goswami; Himesh Shivappa; Bharamanagoudra S. Goud (Meteorologische Zeitschrift, 2010)
The growing worldwide trend in urbanization leading to the development of mega cities is likely to have a strong impact on local weather and climate through a variety of effects like Urban Heat Island (UHI), increased surface heat f ux and atmospheric air temperature. These changes, in turn, can have a signif cant impact on energy demands for cooling or warming. It is, therefore, necessary to study these effects through models that comprehensively describe the local atmospheric dynamics in a large-scale environment. In this work we examine the impact of urbanization on the evolution and dynamics of three heavy rainfall events that occurred over Indian cities (Mumbai, Bangalore and Chennai) in different seasons using the mesoscale atmospheric model MM5, version-3. Numerical experiments were carried out for each of the events using a 3-nest conf guration with a 2 km resolution for the innermost domain. Simulations were carried out for two scenarios; partially urban and fully urban. It was found that urbanization drastically increases maximum surface temperature (ground temperature) for both Mumbai and Chennai event, while for the Bangalore event, the change is mostly in the minimum temperature. In general it was found that urbanization increases the Diurnal Temperature Range (DTR). These differences in temperature, prominent in the pre-rainfall period, dissipate during the event window. Urbanization was also found to increase the temperature throughout the depth of the atmospheric column. Of primary concern is the change in the intensity and duration of extreme weather events. Our results show that increased urbanization affects both intensity and spatial distribution of rain. Partial urbanization was found to be associated with more total rain, larger spatial extend of distribution and less intensity, while the converse is true for the fully urban scenario. The impact of the spatial extant of urbanization (large city vs. megacity) was also examined through an additional set of numerical experiments; the size of the city was found to have a marked inf uence on both the intensity and distribution of rainfall.